Di(naphthalen-2-yl)-1, 2-diphenylethene-based conjugated polymers: aggregation-enhanced emission and explosive detection. Issue 44 (15th October 2015) - Gao, Mengxia; Wu, Yue; Chen, Bin; He, Bairong; Nie, Han; Li, Tingyan; Wu, Fupeng; Zhou, Wenjun; Zhou, Jian; Zhao, Zujin
Abstract : Conjugated polymers with rotatable naphthalen-2-yl pendants show aggregation-enhanced emission characteristics and explosive detection potential. Abstract : Fluorescent conjugated polymers based on a new AIE building block, di(naphthalen-2-yl)-1, 2-diphenylethene, are synthesized and characterized. These polymers show interesting aggregation-enhanced emission and function well in explosive detection in aqueous media.